MANAJEMEN KELAS; DIFERENSIASI LAYANAN INKLUSIF, PENANGANAN KERAGAMAN PESERTA DIDIK - Fahmi; Aziziyah; Willya Oktavia; Suarni Sugandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of classroom management in supporting inclusive differentiated services to address student diversity in educational settings. The study employed a qualitative approach using a library research method by analyzing various scientific sources related to classroom management, differentiated learning, inclusive education, and student diversity. Data were collected through documentation techniques from journals, books, and relevant academic publications published between 2022 and 2026. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that effective classroom management plays a crucial role in creating a conducive, inclusive, and adaptive learning environment that accommodates students' diverse needs. Differentiated learning was found to be an effective strategy for providing inclusive educational services through adjustments in content, process, product, and learning environment based on students' readiness, interests, and learning profiles. Furthermore, the integration of classroom management and differentiated instruction contributes significantly to improving student participation, learning outcomes, social interaction, and educational equity. Despite challenges such as limited teacher competence, inadequate resources, and insufficient institutional support, classroom management and differentiated instruction remain strategic approaches to achieving inclusive, equitable, and quality education for all learners.